Konseling Pancawaskita untuk Membentuk Problem Focused Coping - Eko Sujadi (Jurnal Konseling dan Pendidikan, 2015)
Problem focused coping with needs to be owned by any individual. When in a stressful situation, individuals are oriented in this strategy will seek to address and eliminate the less pleasant atmosphere directly to sources of stress through concrete actions that are positive. The emergence of the stress on the individual factors within or due to the influence of outside forces. Through pancawaskita counseling of individuals need to be aware that he has the power of all of that can be utilized to achieve a life of happiness. Execution of counseling by counselors in pancawaskita form the problem focused coping must be accompanied by a performance and spirit accompanied with intelligence, strength, precision, “keterarahan”, and “kearifbijaksanaan”.